Assessing the Impact of Entrepreneurship Education on the Entrepreneurial Intention of Nigerian Entrepreneurship Students - Amuda, Owoyemi; Zubairu, Umaru Mustapha; Ibrahim, Bello; Maitala, Faiza (International Journal of Education, 2019)
This study investigated the impact of entrepreneurship education on the entrepreneurial intentions (EI) of students enrolled at the Department of Entrepreneurship and Business Studies located in the Federal University of Technology Minna, Nigeria. It employed a cross-section survey design using a questionnaire adapted from Turker Selcuk (2009). A comparison of the mean EI scores of 82 final-year and 68 second-year students revealed that there was no significant difference in entrepreneurial intentions between the two groups of students. This implied that the curriculum of the department needed to be revised, and that a policy of mandating entrepreneurship education at the university level was insufficient to address the alarming youth unemployment problem in Nigeria.